2021
DOI: 10.34172/jrip.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of fecal oxalate-degrading activity in oxalate homeostasis in end-stage renal disease patients; a descriptive pilot study

Abstract: Introduction: End-stage renal disease (ESRD) patients have significant differences in plasma oxalic acid (POx) concentration under the same treatment conditions. Objectives: In the present study, we adopted the method of redoximetric titration with a KMnO4 solution to evaluate the effect of total fecal oxalate-degrading activity (ODA) on oxalate homeostasis in ESRD patients which has never been reported before. Patients and Methods: A total of 56 participants were enrolled in this cross-sectional pilot study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The redoximetric titration with KMnO 4 was adopted to evaluate the total ODA of bacteria in culture media, as described previously [9,24]. In brief, an aliquot of 10 ml test solution and 10 ml Oxalate Medium (control solution) was centrifuged at 3000 g for 15 min at room temperature.…”
Section: Determination Of Odamentioning
confidence: 99%
See 1 more Smart Citation
“…The redoximetric titration with KMnO 4 was adopted to evaluate the total ODA of bacteria in culture media, as described previously [9,24]. In brief, an aliquot of 10 ml test solution and 10 ml Oxalate Medium (control solution) was centrifuged at 3000 g for 15 min at room temperature.…”
Section: Determination Of Odamentioning
confidence: 99%
“…The term of total ODA in fecal microbiota could be de ned as the general ability of different strains of ODB to metabolize oxalate [9]. Several in vitro studies have been devoted to oxalate degradation abilities of Oxalobacter formigenes, Bi dobacterium and Lactobacillus strains in which the e ciency degrade oxalate from 15-98% has been reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the association between dialysis-related peritonitis and oxalate balance in PD patients had never been analyzed before. We have suggested 2 possible pathways of how dialysis-related peritonitis affects oxalate balance in PD patients: 1) the alteration of the peritoneal membrane could decrease the peritoneal clearance of oxalate and, consequently, its removal level, and 2) the use of antibiotics could increase intestinal oxalate absorption and hyperoxalemia (31)(32)(33)(34). The present study focused on the effect of dialysis-related peritonitis on oxalate balance through the reduction of the peritoneal oxalate removal rate in PD patients.…”
Section: Discussionmentioning
confidence: 94%
“…In our previous report, we showed that ODA in fecal microbiota has a direct association with the percentage of renal interstitial fibrosis in rats following glycerol-induced acute kidney injury over 70 days [ 100 ]. In addition, total fecal ODA has been found to be significantly lower in patients with ESKD compared to healthy controls [ 101 , 102 ]. Interestingly, it appears that ODA, rather than the quantity of ODB in the gut microbiota, may have an impact on oxalate homeostasis [ 21 , 102 ].…”
Section: Gut-kidney Axis In Ckd Oxalate Homeostasismentioning
confidence: 99%
“…In addition, total fecal ODA has been found to be significantly lower in patients with ESKD compared to healthy controls [ 101 , 102 ]. Interestingly, it appears that ODA, rather than the quantity of ODB in the gut microbiota, may have an impact on oxalate homeostasis [ 21 , 102 ]. This hypothesis was supported by findings on the inverse association between ODA in fecal microbiota and serum indoxyl sulfate, UOx, and POx concentrations [ 101 , 102 ].…”
Section: Gut-kidney Axis In Ckd Oxalate Homeostasismentioning
confidence: 99%